Interfacial microstructure growth mechanism of lead-free solder using laser soldering - Muhammad Asyraf, Abdullah (2024)
According to scientific evidence, plumbum (Pb) is recognized as a metal with the highest potential for adverse impacts on human health. For that, there was a growing emphasis on green electronics, particularly advanced electronic packaging technology, to promote societal health. As we know, green alloys are considered a safer option for the environment and human health. These alloys are also recognized for their potential for reuse, resulting in cost-effectiveness. This study aims to investigate the impact of different compositions of green solder alloys on the development and growth of intermetallic compounds (IMC) during laser soldering of a metallized copper substrate. Besides that, the solder joint strength was analyzed through mechanical testing. The experiment used Sn and Cu powder with different percentages (Sn-xCu, where x = 0.0, 0.3, 0.5, 0.7, 1.0). In this study, the process starts with materials preparation through powder metallurgy process route. Powder material was weighed and then blended using powder milling at the speed range of 1300-1500 rpm for 3 hours. The mixture of powders was compacted using a pressure of 5 tons to produce thin rectangular pallets with dimensions of 3.2 x 1.5 mm. These pallets were then subjected to laser soldering using a CO2 gas laser, with a laser power of 35 watts, a scanning time of 0.04s, a focal length of 40mm, and a scanning speed of 100mm/s. The substrate employed in the experiment was electroless nickel immersion gold (ENIG). The procedure was further followed by subjecting the samples to isothermal ageing at a temperature of 150oC for durations of 0, 200, 500, 1000, and 2000 hours. After that, these samples were mechanically tested using a shear test, following the ASTM D1002 standard was used to evaluate single-lap-joint adhesively bonded metal specimens (solder alloy). The composition, thickness, and morphology of IMC formed after laser soldering were examined using various material characterization techniques, such as optical and image analysis, scanning electron microscopy, and energy-dispersive X-ray analysis. The study found that the material composition affected the morphology of IMCs, which also influenced their growth behaviour. Increasing the Cu content in the solder alloy decreased the thickness of the IMC, with the lowest thickness observed at 0.3wt% Cu. Nevertheless, the thickness gradually increased with isothermal ageing, and the IMC changed from a needle-shape to a continuous level-off shape. The 0.7wt% Cu solder exhibited the lowest diffusion coefficients and the most effective reduction in IMC growth. The wetting behaviour of Sn-xCu composite solders was significantly affected by Cu particle content, with the lowest wetting angle observed at 0.7wt% Cu. Adding Cu to the solder alloy improved the shear strength of single lap joints, with the highest strength observed at 0.7wt% Cu. However, the shear strength of Sn-0.3Cu joints decreased after isothermal ageing. The combination of powder metallurgy and laser soldering techniques improved the reliability of solder joints in microelectronic production, providing a potential solution for achieving reliability in microelectronic production processes. The study's results demonstrate the effectiveness of this approach in achieving a uniform composition and microstructure of the solder preform, resulting in a superior solder joint with improved mechanical and thermal properties.